2020
DOI: 10.1108/jic-07-2019-0178
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants of scientific productivity: a proposed typology of researchers

Abstract: PurposeAlthough several previous studies were focused on examining the determinants of research productivity, the knowledge of the competences and motives that lead researchers to achieve relevant scientific performance remains unclear. This paper is aimed at contributing to this gap in the research by proposing a typology to understand academic researchers' traits and extending the traditional “more is better” approach, which assumes that higher levels of competence and motivation are always preferable.Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…It has also been suggested that employees who are more motivated by extrinsic factors, such as monetary rewards, will be less productive in their research [ 27 ]. Another study suggested different typologies of researchers with various patterns of intrinsic and extrinsic motivation and association with scientific productivity, which they mean indicated that academics have both extrinsic and intrinsic motives for undertaking research [ 29 ]. The relationship between research productivity and job satisfaction within academia has been extensively studied (e.g., [ 30 , 31 ]), and a positive correlation between productivity and job satisfaction has been reported [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that employees who are more motivated by extrinsic factors, such as monetary rewards, will be less productive in their research [ 27 ]. Another study suggested different typologies of researchers with various patterns of intrinsic and extrinsic motivation and association with scientific productivity, which they mean indicated that academics have both extrinsic and intrinsic motives for undertaking research [ 29 ]. The relationship between research productivity and job satisfaction within academia has been extensively studied (e.g., [ 30 , 31 ]), and a positive correlation between productivity and job satisfaction has been reported [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This counter-intuitive result may be accounted for several factors affecting the productivity of researchers. Again, this might be indicative of the importance of the quality of the human resources, namely in terms of education, competence and motivation (Ballesteros-Rodríguez et al, 2020;De Rassenfosse and de la Potterie, 2009). Perhaps the most compelling explanation, however, may lie in the underlying structures of the different economies, their differing propensities for undertaking R&D and the purposes to which it is put.…”
Section: Appendix a Supplementary Datamentioning
confidence: 99%
“…It can activate, maintain, and regulate scientific research behavior [ 40 ]. Research motivation is the psychological motivation that influences scholars to participate in scientific research [ 41 ]. It stems from scholars’ own scientific research interests, scientific research ideals, and social responsibilities [ 42 ].…”
Section: Research Propositions and Hypothesesmentioning
confidence: 99%